2017
DOI: 10.1007/s40263-017-0436-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Muscarinic M3 Receptor Antagonism on the Risk of Type 2 Diabetes in Antidepressant-Treated Patients: A Case-Controlled Study

Abstract: BackgroundM3 muscarinic receptor antagonism has been associated with glucose intolerance and disturbance of insulin secretion.ObjectiveOur objective was to examine the risk of type 2 diabetes mellitus (T2DM) in patients using antidepressants with and without M3 muscarinic receptor antagonism (AD_antaM3 and AD_nonantaM3, respectively).MethodsWe designed a case–control study using a pharmacy prescription database. We selected a cohort of patients who initiated antidepressant use between the ages of 20 and 40 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…An inverse association between the inhibitory constant (Ki) for H 1 and prevalence of metabolic syndrome was also observed [6]. In addition, a case-control study suggested that antidepressants with antagonistic properties on M 3 are associated with incident type 2 diabetes [7]. A disproportionality analysis in the pharmacovigilance database of the WHO has also suggested that antidepressants might associate with diabetes, with a more pronounced risk for antidepressants with affinities to H 1 , 5-HT 2C and NET [5].…”
Section: Figurementioning
confidence: 92%
See 1 more Smart Citation
“…An inverse association between the inhibitory constant (Ki) for H 1 and prevalence of metabolic syndrome was also observed [6]. In addition, a case-control study suggested that antidepressants with antagonistic properties on M 3 are associated with incident type 2 diabetes [7]. A disproportionality analysis in the pharmacovigilance database of the WHO has also suggested that antidepressants might associate with diabetes, with a more pronounced risk for antidepressants with affinities to H 1 , 5-HT 2C and NET [5].…”
Section: Figurementioning
confidence: 92%
“…A recent pharmacoepidemiological-pharmacodynamic study in VigiBase suggested that antipsychotics with H 1 and 5-HT 2C antagonistic properties were associated with diabetes [4]. Similar receptor mechanisms could mediate antidepressant-induced metabolic side effects; in support, observational studies suggested that NET inhibition, as well as antagonism on 5-HT 2C , H 1 [5,6] and M 3 receptors [7], could explain the risk for diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, doxepin-treated animals have been noted to have increased insulin sensitivity (IS); thus, doxepin may regulate glucose metabolism through Akt activation enhancement and gluconeogenesis suppression [ 28 , 29 ]. However, in patients using antipsychotics, doxepin can lead to hyperglycemia and exacerbate preexisting diabetes, hypertriglyceridemia, and hypercholesterolemia [ 30 , 31 , 32 ], but it can be an effective treatment option for postprandial hypoglycemia [ 33 ]. Long-term doxepin use can also induce NAFLD-associated body weight gain [ 34 ] and liver injury [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prescription data from hospital and OTC drugs are not included in this database. The IADB.nl has been used as a reliable source of data for many pharmacoepidemiological researches …”
Section: Methodsmentioning
confidence: 99%
“…nl has been used as a reliable source of data for many pharmacoepidemiological researches. [19][20][21]…”
Section: Settingmentioning
confidence: 99%